Gymnogeophagus caaguazuensis - Alonso, Felipe (2022)
Gymnogeophagus caaguazuensis has most recently been assessed for The IUCN Red List of Threatened Species in 2020. Gymnogeophagus caaguazuensis is listed as Endangered under criteria B1ab(iii)+2ab(iii).